2019
DOI: 10.1155/2019/6109758
|View full text |Cite
|
Sign up to set email alerts
|

Stable Copper Tin Sulfide Nanoflower Modified Carbon Quantum Dots for Improved Supercapacitors

Abstract: Copper tin sulfides (CTSs) have widely been investigated as electrode materials for supercapacitors owing to their high theoretical pseudocapacitances. However, the poor intrinsic conductivity and volume change during redox reactions hindered their electrochemical performances and broad applications. In this study, carbon quantum dots (CQDs) were employed to modify CTSs. e structures and morphologies of obtained materials were characterized by X-ray diffraction (XRD) and transmission electron microscopy (TEM).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 28 publications
0
4
1
Order By: Relevance
“…Overall, the significance and novelty lie in potential of Cu2FeBiS4 to offer comparable or even superior catalytic performance while overcoming the limitations associated with the scarcity and high cost of noble metals, thus paving the way for sustainable and scalable electrochemical applications. The outcomes of this research revealed a remarkable enhancement in specific capacitance of CFBS capacitance of (1530 F/g), obscuring previously reported results for CuFeS2 (537 F/g) [27] and Cu2SnS3 (856 F/g) [28] and the robustness and utility of the CFBS electrode is underscored by its exceptional stability, having a retention rate of 74% even after undergoing 1000 charge-discharge cycles at an elevated rate of 5 A/g. This endurance highlights the potential viability of electrodes for steadfast integration within energy storage systems.…”
Section: Introductioncontrasting
confidence: 97%
“…Overall, the significance and novelty lie in potential of Cu2FeBiS4 to offer comparable or even superior catalytic performance while overcoming the limitations associated with the scarcity and high cost of noble metals, thus paving the way for sustainable and scalable electrochemical applications. The outcomes of this research revealed a remarkable enhancement in specific capacitance of CFBS capacitance of (1530 F/g), obscuring previously reported results for CuFeS2 (537 F/g) [27] and Cu2SnS3 (856 F/g) [28] and the robustness and utility of the CFBS electrode is underscored by its exceptional stability, having a retention rate of 74% even after undergoing 1000 charge-discharge cycles at an elevated rate of 5 A/g. This endurance highlights the potential viability of electrodes for steadfast integration within energy storage systems.…”
Section: Introductioncontrasting
confidence: 97%
“…Carbon dots (CDs) of several nanometers could be in situ doped into MoS 2 , Ni/Co/P, SrRuO 3 , and other nanocrystals, enhancing their conductivity and electrochemical activity. Lately, Bao et al successfully prepared the CD-doped α-Co/Ni­(OH) 2 hollow nanocages with enhanced energy storage performance, where CDs were clearly observed among Ni­(OH) 2 grains . These investigations indicate that CDs are feasible as suitable dopants to regulate the stack growth of Ni­(OH) 2 nanocrystals.…”
Section: Introductionmentioning
confidence: 99%
“…It has maintained a high reversible specific capacity of 420 mAh g -1 after 200 cycles at 0.2 A g -1 . The study has revealed that the CEM assists to improve the electrochemical properties of SnO 2 especially in cyclic ability [106].…”
Section: Carbon Quantum Dotsmentioning
confidence: 97%
“…Transition metal sulfides (TMSs) such as CuS, Cu 2 S, SnS 2 , SnS, MoS 2 , FeS 2 , TiS 2 , and CoS 2 are considered as promising anode materials for Na-ion batteries due to their large specific capacities and weak bonding between metal (M) and sulfide (S) which favors conversion reactions [106]. In this the replacement of oxygen with sulfur, an element with a low electronegativity shows better performance when compared to that of transition metal oxides (TMOs).…”
Section: Carbon Quantum Dotsmentioning
confidence: 99%